The Effect of Discipline and Work Motivation on Teacher Performance at Al-Ihsaniyah Foundation Kramat Jati East Jakarta - Sri Wulandari; Muji Rahayu (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the influence of discipline and work motivation on teacher performance at the Al-Ihsaniyah Kramat Jati Foundation, East Jakarta. This research uses a quantitative approach. This research was conducted on March 1 2024 at the Al-Ihsaniyah Kramat Jati Foundation, East Jakarta. The respondents in this research were teachers at the Al-Ihsaniyah Kramat Jati Foundation, East Jakarta, totaling 45 respondents. The sampling technique in this research is saturated sampling. The data collection technique uses a questionnaire. The research results show that there is a positive and significant influence of discipline and work motivation on teacher performance at the Al-Ihsaniyah Kramat Jati Foundation, East Jakarta, both partially and simultaneously. High motivation can encourage teachers to face challenges with enthusiasm and determination, increase involvement in the learning process, and motivate them to continue to improve the quality of their teaching. On the other hand, consistent work discipline ensures that teachers allocate their time and energy effectively to lesson preparation, interaction with students, and professional development, which directly impacts the quality of learning delivered and student outcomes. Therefore, managing motivation and work discipline is important in building a productive learning environment and increasing student achievement.